Anti-union or pro-property? Worker surveillance and gold theft in Western Australia gold mines, 1899-1920 - Segal, Naomi (Australian Society for the Study of Labour History, 2009)
Historically, both in Australia and elsewhere, employers often used blacklists to exclude unionists from their workforce. In Western Australia, workers in the first decades of the gold mining industry feared such an 'organised system of victimisation' as early as 1903. This paper is a first step in examining whether the umbrella body, the Chamber of Mines of Western Australia, in developing and operating a system for surveilling workers to prevent gold stealing, extended the surveillance also to workers it considered undesirable for political or industrial reasons, as workers feared. The paper investigates the emergence of the system of blacklisting 'undesirable employees' on the mines and the nature, the extent and intent of intelligence collecting and sharing by mine employers. However, as it was possible to access only a small fraction of the records pertaining to the surveillance operation (the remainder are still restricted), the paper's conclusion are only tentative.